Multifunctional Phosphorescent Conjugated Polymer Dots for Hypoxia Imaging and Photodynamic Therapy of Cancer Cells. Issue 2 (10th September 2015) - Zhou, Xiaobo; Liang, Hua; Jiang, Pengfei; Zhang, Kenneth Yin; Liu, Shujuan; Yang, Tianshe; Zhao, Qiang; Yang, Lijuan; Lv, Wen; Yu, Qi; Huang, Wei
Abstract : Molecular oxygen (O2 ) plays a key role in many physiological processes, and becomes a toxicant to kill cells when excited to 1 O2 . Intracellular O2 levels, or the degree of hypoxia, are always viewed as an indicator of cancers. Due to the highly efficient cancer therapy ability and low side effect, photodynamic therapy (PDT) becomes one of the most promising treatments for cancers. Herein, an early‐stage diagnosis and therapy system is reported based on the phosphorescent conjugated polymer dots (Pdots) containing Pt(II) porphyrin as an oxygen‐responsive phosphorescent group and 1 O2 photosensitizer. Intracellular hypoxia detection has been investigated. Results show that cells treated with Pdots display longer lifetimes under hypoxic conditions, and time‐resolved luminescence images exhibit a higher signal‐to‐noise ratio after gating off the short‐lived background fluorescence. Quantification of O2 is realized by the ratiometric emission intensity of phosphorescence/fluorescence and the lifetime of phosphorescence. Additionally, the PDT efficiency of Pdots is estimated by flow cytometry, MTT cell viability assay, and in situ imaging of PDT induced cell death. Interestingly, Pdots exhibit a high PDT efficiency and would be promising in clinical applications. Abstract : Water‐soluble and multifunctional phosphorescent conjugated polymer dots, containing Pt(II) porphyrin as an oxygen‐responsive phosphorescent group and 1 O2 photosensitizer, are reported. These polymer dots (Pdots) are used for ratiometric and time‐resolved luminescence imaging of hypoxia in living cells. Additionally, as a singlet oxygen photosensitizer, the Pdots exhibit highly efficient photodynamic therapy of cancer cells.